Mitigation for noise interference in vector sensor test bench - Chin, Sonia Foong (2016)
Accelerometers is an electromechanical device that senses vibration and acoustic frequencies which behaves like a SONAR (Sound Navigation and Ranging) system. For this particular project, a Piezoelectric Accelerometer is used. This device will be installed on an underwater vehicle where it will be used for underwater communication or noise detection and vibration measurements. This would be highly useful and beneficial in an event where intruders enter or cross a country border. Before the accelerometers are installed onto the underwater vehicle, it has to undergo testing procedures. As for this project, it involves 2 piezoelectric accelerometers for the test. The 2 piezoelectric accelerometers consists of a calibrated accelerometer which is used as a reference and the actual accelerometer (device under test) which will be installed on the underwater vehicle. Due to either electrical or mechanical setup, the frequency response of the actual accelerometer does not follow the calibrated response which has a typical ideal frequency response shown in Appendix A. Instead, the actual accelerometer frequency response displays noise signals being produced when supplied by a DC power supply. Therefore, with this setback, the purpose of this project is to primarily focus on identifying the mechanical noise contributors in the test bench set-up and find a solution to overcome the noise signals. Hence, this final report delivers the process of researched, designs, building, implementation and lastly discussing the results.